Preparation method and application of nickel-manganese-based catalyst
Nickel-manganese-based catalysts were prepared on nickel foam substrates by impregnation, which solved the problem of high cost of precious metal catalysts. This method achieved high selectivity and stability in the high-efficiency electrocatalytic oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid, and is suitable for electrocatalytic reactions in alkaline electrolytes.
Patent Information
- Application Number
- CN202511433870.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-09
- Publication Date
- 2025-12-23
Smart Images

Figure CN121183371A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of electrocatalyst preparation, and more particularly relates to a preparation method of a nickel-manganese-based catalyst and application thereof. BACKGROUND
[0002] To break through the dilemma of fossil energy dependence, sustainable clean hydrogen production technology based on water electrolysis has attracted much attention. Among them, the anodic oxygen evolution reaction needs to apply a high overpotential to drive the reaction due to its complex multi-step mechanism, which directly leads to a significant reduction in system energy conversion efficiency. Recent studies have shown that using biomass platform molecules and their derivatives to replace the traditional oxygen evolution process can not only obtain high-purity hydrogen and commercially valuable organic oxidation products simultaneously, but more importantly, significantly improve the overall energy conversion efficiency by reducing the reaction overpotential. This coupling electrocatalysis strategy provides an innovative approach to building a new “hydrogen-chemicals” co-production system.
[0003] Under the framework of green industrial revolution driving carbon neutralization transformation, building an efficient biomass platform molecule electrocatalytic conversion system is becoming a key strategy to break through the traditional energy path. Further oxidation of biomass raw material 5-hydroxymethylfurfural (5-HMF) can obtain 2,5-furan dicarboxylic acid (FDCA) with high added value. This compound has structural similarity with petroleum-based terephthalic acid and can be used as a new monomer for polyester material synthesis, significantly reducing the dependence of the chemical industry on fossil resources.
[0004] Electrocatalytic oxidation of 5-HMF has the following advantages: (1) low reaction temperature and pressure, usually under ambient conditions; (2) relatively short reaction time; (3) water can be used as an oxygen source, avoiding the introduction of O2, and ensuring the safety of operation; (4) the reaction rate and selectivity of the product can be accurately controlled by reasonably adjusting the electrode potential and circuit current; (5) paired electrosynthesis can be carried out, such as producing high-value chemicals from both the anode and the cathode. Although noble metals have a lower activation potential in the electrocatalytic oxidation of HMF to prepare FDCA, the current density is low and the cost is high, so how to prepare a catalyst that can electrocatalytically oxidize HMF to prepare FDCA with high selectivity in alkaline electrolyte has become a difficult problem that technicians in the field need to overcome. SUMMARY
[0005] The purpose of the present application is to provide a preparation method of a nickel-manganese-based catalyst and application thereof, and more particularly to provide a preparation method of a nickel-manganese-based electrocatalytic oxidation 5-hydroxymethylfurfural catalyst and application thereof to solve the problems existing in the prior art.
[0006] To achieve the above purpose, the present application provides the following solutions:
[0007] One of the technical solutions of the present application: a preparation method of a nickel-manganese-based catalyst, the steps comprising:
[0008] Dissolve the nickel source in an organic solvent, and perform a hydrothermal reaction to form a nickel-based active layer on a nickel foam substrate;
[0009] Then, perform liquid-phase impregnation treatment on the nickel foam substrate with the nickel-based active layer in an aqueous solution containing a manganese source and a regulator, and obtain the nickel-manganese-based catalyst after drying;
[0010] The regulator comprises at least one of sodium thiosulfate, thiourea, and sodium sulfide.
[0011] Further, the nickel source comprises at least one of nickel nitrate, nickel chloride, and nickel acetate.
[0012] Further, the organic solvent comprises N,N-dimethylformamide and / or ethanol, and the volume ratio is 10:0-0:10.
[0013] Further, the molar number of the nickel source dissolved in 12 mL of the organic solvent is 0.4-2.4 mmol.
[0014] Further, the temperature of the hydrothermal reaction is 100-180 ℃, and the time is 8-24 h.
[0015] Further, the manganese source in the aqueous solution containing the manganese source and the regulator comprises at least one of manganese nitrate, manganese chloride, and manganese acetate.
[0016] Further, in the aqueous solution containing the manganese source and the regulator, the content of deionized water is 40 mL, the addition amount of the manganese source is 0.6 mmol, and the addition amount of the regulator is 0.9 mmol.
[0017] Further, the pH of the aqueous solution containing the manganese source and the regulator is 9-12.
[0018] Further, the time of the liquid-phase impregnation treatment is 8-24 h.
[0019] The present application adopts the impregnation method to prepare the catalytic material and the functional material, which is simple in operation, low in equipment requirement, easy to repeat and enlarge production. The present application makes full use of the characteristics of the three-dimensional interpenetrating porous structure and large specific surface area of the nickel foam (NF), so that the precursor solution can fully penetrate into the pores inside the NF, which helps the high dispersion of the nanoparticles on the nickel foam skeleton, prevents agglomeration, and realizes the bulk loading, which greatly increases the number of active sites. In the impregnation process, a strong interaction (such as chemical bond, electrostatic adsorption, etc.) is formed between the active component precursor and the surface of the carrier, so that the active component can be firmly attached to the carrier and is not easy to fall off during use, further ensuring the stability of the electrode.
[0020] The present application places a foamed nickel substrate in a mixed solution of a nickel source and an organic solvent, carries out a hydrothermal synthesis reaction, and after drying treatment, the material is immersed in a mixed aqueous solution of a manganese source and a conditioning agent, and the pH of the solution is adjusted, and finally a nickel-manganese-based electrocatalyst is obtained. The preparation method is simple, low in price, and the prepared catalyst exhibits high catalytic activity, high FDCA selectivity, high faradic efficiency and excellent stability, and has great industrial application prospect.
[0021] The second technical scheme of the present application provides a nickel-manganese-based catalyst prepared by the above preparation method.
[0022] The third technical scheme of the present application provides an application of the above nickel-manganese-based catalyst in the electrocatalytic oxidation of 5-hydroxymethylfurfural to prepare 2,5-furan dicarboxylic acid.
[0023] The nickel-manganese-based catalyst provided by the present application does not require the participation of noble metals, is low in cost, can be produced on a large scale, has a 5-hydroxymethylfurfural (HMF) conversion rate of more than 93%, a 2,5-furan dicarboxylic acid (FDCA) yield of more than 95%, and a faradic efficiency of more than 92%.
[0024] The fourth technical scheme of the present application provides a method for electrocatalytically oxidizing 5-hydroxymethylfurfural to prepare 2,5-furan dicarboxylic acid, wherein the above nickel-manganese-based catalyst is used as a working electrode or working electrode modification material.
[0025] The present application discloses the following technical effects:
[0026] The present application prepares a high-efficiency electrocatalyst based on foamed nickel, which can be directly used as a working electrode, and provides a three-dimensional network porous structure for electrocatalytic reaction. Under the action of an electric field, NiOOH generated in the nickel-manganese-based catalyst is an active site for the oxidation of 5-hydroxymethylfurfural. The addition of Mn can promote the generation of high-valence nickel and thus promote the generation of NiOOH, and HMF can be electrocatalytically oxidized in an alkaline electrolyte to prepare FDCA with high selectivity.
[0027] In the preparation process of the present application, the nickel source is dissolved in an N,N-dimethylformamide and / or ethanol solution, a sheet-shaped reaction active layer is formed on the surface of the foamed nickel by a hydrothermal method, and then the nickel-based catalyst is immersed in a mixed solution of a manganese source and a conditioning agent (such as sodium thiosulfate) to obtain a nickel-manganese-based catalyst. In the presence of Mn, more high-valence nickel is formed in the catalyst, which is beneficial to the generation of NiOOH, thereby effectively improving the performance of the electrocatalyst.
[0028] The prepared nickel-manganese-based catalyst realizes 93.9% of HMF conversion rate, 96.5% of FDCA yield and 95.6% of Faraday efficiency. After 5 cycles, the high HMF conversion rate, FDCA yield and Faraday efficiency can still be maintained, and the nickel-manganese-based catalyst has wide application prospect. BRIEF DESCRIPTION OF DRAWINGS
[0029] The accompanying drawings, which form a part of the present description, are included to provide further understanding of the application and are incorporated in and constitute a part of this specification, illustrate exemplary embodiments of the present application and serve to explain the principles of the present application. In the drawings:
[0030] Figure 1 Cycle stability chart for B1 catalyst.
[0031] Figure 2 Liquid chromatogram of HMF, FDCA, FFCA, HMFCA and DFF.
[0032] Figure 3 LSV chart of NiO-Mn3O4 / NF catalyst in 1.0 M KOH solution containing and not containing 0.02 M HMF, and NiO / NF and Mn3O4 / NF in 1.0 M KOH solution containing 0.02 M HMF.
[0033] Figure 4 Double-layer capacitance value C of NiO-Mn3O4 / NF, NiO / NF and Mn3O4 / NF catalyst dl value.
[0034] Figure 5 Nyquist chart of NiO-Mn3O4 / NF, NiO / NF and Mn3O4 / NF catalyst DETAILED DESCRIPTION
[0035] Various exemplary embodiments of the present application will now be described in detail, which should be considered to be illustrative of the application and are not intended to limit the scope of the application. It should be understood that many modifications and variations of the exemplary embodiments of the applications are possible, as will be appreciated by those skilled in the art.
[0036] It should be understood that the terms used in the present application are merely used to describe particular embodiments and are not intended to limit the present application. In addition, for the numerical range in the present application, it should be understood that each intermediate value between the upper limit and the lower limit of the range is also specifically disclosed. Each smaller range within the range of the intermediate values in any stated value or stated range, and any other stated value or intermediate value within the stated range are also included in the present application. The upper limit and the lower limit of these smaller ranges can be independently included or excluded from the range.
[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as those commonly understood by one of ordinary skill in the art to which this application pertains. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present application, the preferred methods and materials are described. All documents mentioned herein are incorporated by reference to disclose and describe in full the methods and / or materials which are described therein. In case of conflict between the present specification and any document incorporated herein by reference, the present specification will control.
[0038] Many modifications and variations of the present application described in the specific embodiments of the application can be made by those skilled in the art without departing from the spirit or scope of the application. Other implementations of the application will be apparent to those skilled in the art from consideration of the specification and practice of the application. The specification and examples are illustrative only.
[0039] As used herein, the terms "comprises", "comprising", "includes", "including", "has", "having", and the like are open-ended terms that are intended to mean including, but not limited to.
[0040] Unless otherwise specified, the raw materials and reagents involved in the specific embodiments of the present application are commercially available.
[0041] Unless otherwise specified, the room temperature and normal temperature involved in the specific embodiments of the present application both refer to 20-30 ℃.
[0042] It should be noted that the present application does not detail the means of routine operation in the art, and is not the focus of the present application.
[0043] Example 1
[0044] The preparation steps of the nickel-manganese-based catalyst include:
[0045] S1, the foamed nickel is pretreated by ultrasonic in acetone and hydrochloric acid, the pretreated foamed nickel is cleaned by ultrasonic with water and ethanol, and then dried for use;
[0046] S2, N,N-dimethylformamide and ethanol are mixed according to the volume ratio of 5:1, the total volume is 12 mL, then nickel nitrate is added and dissolved to obtain a mixed solution;
[0047] Among them, the amount of nickel nitrate added in the mixed solution is 1.6 mmol;
[0048] S3, the mixed solution obtained in step S2 is transferred to a hydrothermal synthesis kettle, then the pretreated foamed nickel in step S1 is also placed in the hydrothermal kettle, sealed, the hydrothermal kettle is placed in a blast drying oven, the hydrothermal temperature is set to 120 ℃, the hydrothermal time is 12 h, a sheet-shaped reactive layer is formed on the foamed nickel substrate, which is denoted as A1;
[0049] S4, manganese nitrate and sodium thiosulfate were added to 40 mL of deionized water in a molar ratio of 1:1.5, and then ammonia water was used to adjust the pH to 12 to obtain an impregnation solution;
[0050] The amount of manganese nitrate added to the impregnation solution was 0.6 mmol.
[0051] S5, the foam nickel substrate on which the sheet-shaped reactive layer was formed obtained in step S3 was placed in the impregnation solution obtained in step S4, and liquid-phase impregnation was performed for 12 h, followed by drying, to obtain a nickel-manganese-based catalyst NiO-Mn3O4 / NF, denoted as B1.
[0052] Example 2
[0053] The preparation steps of the nickel-manganese-based catalyst included:
[0054] S1, the foam nickel was pretreated by ultrasonic treatment in acetone and hydrochloric acid, and the treated foam nickel was cleaned with water and ethanol and then dried for use;
[0055] S2, N,N-dimethylformamide and ethanol were mixed in a volume ratio of 5:1, with a total volume of 12 mL, and then nickel nitrate was added and dissolved to obtain a mixed solution;
[0056] The amount of nickel nitrate added to the mixed solution was 0.4 mmol.
[0057] S3, the mixed solution obtained in step S2 was transferred to a hydrothermal synthesis kettle, and then the foam nickel treated in step S1 was also placed in the hydrothermal kettle, which was sealed and placed in a forced air drying oven, and the hydrothermal temperature was set to 120°C and the hydrothermal time was 12 h, forming a sheet-shaped reactive layer on the foam nickel substrate, denoted as A2;
[0058] S4, manganese nitrate and sodium thiosulfate were added to 40 mL of deionized water in a molar ratio of 1:1.5, and then ammonia water was used to adjust the pH to 12 to obtain an impregnation solution;
[0059] The amount of manganese nitrate added to the impregnation solution was 0.6 mmol.
[0060] S5, the foam nickel substrate on which the sheet-shaped reactive layer was formed obtained in step S3 was placed in the impregnation solution obtained in step S4, and liquid-phase impregnation was performed for 12 h, followed by drying, to obtain a nickel-manganese-based catalyst, denoted as B2.
[0061] Comparative Example 1
[0062] The preparation steps of the electrocatalyst included (S2, S3 in the examples were reduced)
[0063] S1, the foamed nickel is ultrasonically pretreated in acetone and hydrochloric acid, the treated foamed nickel is ultrasonically cleaned with water and ethanol and then dried for standby use;
[0064] S2, manganese nitrate and sodium thiosulfate are added into 40 mL deionized water according to a molar ratio of 1:1.5, and then ammonia water is used to adjust the pH to 12, so as to obtain an impregnation solution;
[0065] The addition amount of manganese nitrate in the impregnation solution is 0.6 mmol.
[0066] S3, the foamed nickel treated in step S1 is placed in the impregnation solution obtained in step S2, and liquid-phase impregnation is performed for 12 h, and then drying is performed, so as to obtain an electrocatalyst Mn3O4 / NF, which is denoted as B3.
[0067] Comparative Example 2
[0068] The preparation steps of the catalyst include: (steps S4 and S5 in the reduced example)
[0069] S1, the foamed nickel is ultrasonically pretreated in acetone and hydrochloric acid, the treated foamed nickel is ultrasonically cleaned with water and ethanol and then dried for standby use;
[0070] S2, nickel nitrate is dissolved in 12 mL water to obtain a nickel nitrate aqueous solution;
[0071] The addition amount of nickel nitrate in the nickel nitrate aqueous solution is 1.6 mmol.
[0072] S3, the nickel nitrate aqueous solution obtained in step S2 is transferred into a hydrothermal synthesis kettle, and then the foamed nickel treated in step S1 is also placed in the hydrothermal kettle, which is sealed, the hydrothermal kettle is placed in a forced air drying oven, the hydrothermal temperature is set to 120 DEG C, the hydrothermal time is 12 h, a reaction active layer is formed on the foamed nickel substrate, which is denoted as A3, and an electrocatalyst NiO / NF is obtained after drying, which is denoted as B4.
[0073] Comparative Example 3
[0074] The preparation steps of the electrocatalyst include: (the difference lies in the solvent of step S2 in the example)
[0075] S1, the foamed nickel is ultrasonically pretreated in acetone and hydrochloric acid, the treated foamed nickel is ultrasonically cleaned with water and ethanol and then dried for standby use;
[0076] S2, nickel nitrate is dissolved in 12 mL deionized water to obtain a nickel nitrate aqueous solution;
[0077] The addition amount of nickel nitrate in the nickel nitrate aqueous solution is 1.6 mmol.
[0078] S3, transfer the nickel nitrate aqueous solution obtained in step S2 into a hydrothermal synthesis kettle, then put the foamed nickel treated in step S1 into the hydrothermal kettle, seal, place the hydrothermal kettle in a forced air drying oven, set the hydrothermal temperature to 120°C, and hydrothermal time to 12 h, to form a reaction active layer on the foamed nickel substrate, denoted as A4;
[0079] S4, add manganese nitrate and sodium thiosulfate into 40 mL deionized water according to a molar ratio of 1:1.5, then adjust the pH to 12 with ammonia water to obtain an impregnation solution;
[0080] wherein the amount of manganese nitrate added in the impregnation solution is 0.6 mmol;
[0081] S5, place the foamed nickel substrate with the formed sheet-like reaction active layer obtained in step S3 into the impregnation solution obtained in step S4, and perform liquid phase impregnation for 12 h, and then dry to obtain an electrocatalyst, denoted as B5.
[0082] Test Example
[0083] Electrochemical performance test of the prepared catalyst for electrocatalytic oxidation of HMF:
[0084] All electrochemical performance tests were performed using a CHI 660e electrochemical workstation with a three-electrode system under normal temperature and pressure. The catalyst prepared in the examples and comparative examples was used as the working electrode, the counter electrode was a platinum sheet electrode, and the reference electrode was a Hg / HgO electrode.
[0085] Before testing, the working electrode needs to be activated by cyclic voltammetry (CV).
[0086] Test items include linear sweep voltammetry curve (LSV), double-layer capacitance test (C dl ), and alternating current impedance test (EIS). LSV test was performed in 10 mL 1.0 M KOH electrolyte containing 0.02 M HMF. This test is mainly used to evaluate the redox performance of the catalyst with and without HMF. The double-layer capacitance test was performed using the CV method in the non-faradic region at different scan rates. The current density Δj at the average value of the potential window was taken as the vertical coordinate, and the scan rate was taken as the horizontal coordinate, and the slope C dl was obtained by linear fitting. EIS test was performed in 10 mL 1.0 M KOH solution with a concentration of 0.02 M HMF, a fixed potential was applied, the frequency range was 0.01~1×10 5 Hz, and the waiting time was 30 s before testing. Through fitting analysis, the impedance values of the electrode surface and the electrochemical reaction process can be obtained. The current density of all tests was normalized by the geometric area of the working electrode.
[0087] All the experimental voltage data were normalized by Nernst equation, with Hg / HgO electrode as reference electrode, and finally converted to reversible hydrogen electrode (RHE) scale:
[0088] E(RHE)=E(Hg / HgO)+0.059pH+0.098
[0089] The potentiostatic HMF electrocatalytic oxidation performance test was carried out at a potential of 1.52 V RHE , and the specific process was as follows: the oxidation degradation of HMF was carried out in an H-type cell at room temperature, and Nafion N117 membrane was used to separate the cathode chamber and the anode chamber. The anode chamber was Hg / HgO reference electrode and working electrode, and the solution was 30 mL of 1.0 M KOH and 0.01 M HMF. The cathode chamber was a 2×2 cm 2 Pt electrode, and the solution was 30 mL of 1.0 M KOH. During the electrolysis process, 100 μL of electrolyte was taken out, neutralized with 100 μL of 1 M hydrochloric acid, and then 800 μL of mobile phase (acetonitrile:acetic acid=10:90) was added. HMF and 5-hydroxymethyl-2-furancarboxylic acid (HMFCA), 5-formyl-2-furancarboxylic acid (FFCA), 2,5-diformylfuran (DFF), and 2,5-furandicarboxylic acid (FDCA) in the electrocatalytic oxidation process were analyzed quantitatively by LC-20A liquid chromatograph of Shimadzu Company, using Shim-pack A227-20742.08 chromatographic column at room temperature.
[0090] The peak values obtained from the HPLC chromatogram were automatically integrated, and then quantitative analysis was carried out according to the standard curve of each substance, to obtain the molar concentration of the substrate and the product generated by electrolysis, which was used to calculate the HMF conversion rate, FDCA yield and Faraday efficiency. The specific calculation formulas are shown in formulas (1-1), (1-2) and (1-3).
[0091] (1-1);
[0092] (1-2);
[0093] (1-3);
[0094] Wherein, F represents Faraday constant (96485 C·mol -1 ), and Q is the number of charges (C) transferred by HMF in the process of being oxidized and degraded.
[0095] Table 1 HMF conversion rate, FDCA yield and Faraday efficiency in the comparative examples and examples
[0096] Catalyst HMF conversion / % FDCA yield / % Faradaic efficiency / % B1 93.9 96.5 95.6 B2 90.7 93.7 92.8 B3 86.1 91.9 91.5 B4 82.1 88.3 84.8 B5 84.7 91.2 90.6
[0097] Table 1 is the HMF conversion, FDCA yield and corresponding Faraday efficiency of the above examples and comparative examples.
[0098] Figure 1 The figure is the cycle stability of B1 catalyst. As can be seen from the figure, the catalyst prepared by the present application has stable HMF conversion, FDCA yield and Faraday efficiency in five cycles, and the specific values are shown in Table 2.
[0099] Table 2
[0100] Cycle number HMF conversion / % FDCA yield / % Faradaic efficiency / % 1 93.9 96.5 95.6 2 93.0 96.3 95.3 3 94.4 97.9 96.4 4 95.2 95.9 92.4 5 94.1 98.6 93.7
[0101] Figure 2 The figure is the liquid chromatogram of 5-hydroxymethylfurfural (HMF) and its oxidation products 2,5-furan dicarboxylic acid (FDCA), 5-formyl-2-furan carboxylic acid (FFCA), 5-hydroxymethyl-2-furan carboxylic acid (HMFCA) and 2,5-diformylfuran (DFF).
[0102] Figure 3 The figure is the LSV curve of NiO-Mn3O4 / NF catalyst in 1.0 M KOH solution with and without 0.02 M HMF, and NiO / NF and Mn3O4 / NF in 1.0 M KOH solution with 0.02 M HMF. As can be seen from the figure, by comparing the LSV curves of NiO-Mn3O4 / NF, NiO / NF and Mn3O4 / NF catalysts in 1.0 M KOH solution with 0.02 M HMF, it can be seen that the NiO-Mn3O4 / NF catalyst maintains a high current density throughout the process of catalytic oxidation of HMF, and the current density can reach 146 mA·cm RHE at 1.52 V -2 and the current density at the same voltage is much higher than that of NiO / NF and Mn3O4 / NF, which indicates that the NiO-Mn3O4 / NF catalyst has stronger oxidation dynamics for the oxidation of HMF. The linear sweep voltammetry curve can directly show that the performance of the NiO-Mn3O4 / NF catalyst is more excellent
[0103] Figure 4 The figure is the double-layer capacitance value C dl of NiO-Mn3O4 / NF, NiO / NF and Mn3O4 / NF catalysts. As can be seen from the figure, the C dl of NiO-Mn3O4 / NF is 1.51 mF·cm -2 , which is higher than the C dl of NiO / NF, which is 0.78 mF·cm -2C of Mn304 / NF dl 0.87 mF·cm -2 It is illustrated that there are more active sites in NiO-Mn304 / NF, which increases the performance of the catalyst for the electrocatalytic oxidation of HMF.
[0104] Figure 5 Nyquist plots of NiO-Mn304 / NF, NiO / NF and Mn304 / NF catalysts. It can be seen from the figure that the diameters of the Faraday semicircles of NiO-Mn304 / NF, NiO / NF and Mn304 / NF have obvious differences. In comparison, the diameter of the Faraday semicircle of NiO-Mn304 / NF is smaller, which indicates that the corresponding impedance is smaller at 1.22 V RHE It can be known that NiO-Mn304 / NF has better electrical conductivity and faster electron transfer efficiency.
[0105] The various embodiments in the specification are described in a progressive manner, and each embodiment focuses on the difference from other embodiments. The same or similar parts between the various embodiments can be referred to each other.
[0106] The above description of the disclosed embodiments enables a person skilled in the art to implement or use the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a nickel-manganese-based catalyst, characterized in that the step... include: The nickel source is dissolved in an organic solvent and subjected to a hydrothermal reaction to form a nickel-based active layer on a nickel foam substrate; The nickel foam substrate forming the nickel-based active layer is then subjected to liquid-phase impregnation treatment in an aqueous solution containing a manganese source and a regulator, and dried to obtain a nickel-manganese-based catalyst. The regulator includes at least one of sodium thiosulfate, thiourea, and sodium sulfide.
2. The preparation method according to claim 1, characterized in that, The nickel source includes at least one of nickel nitrate, nickel chloride, and nickel acetate.
3. The preparation method according to claim 1, characterized in that, The organic solvent includes N,N-dimethylformamide and / or ethanol in a volume ratio of 10:0 to 0:
10.
4. The preparation method according to claim 1, characterized in that, The nickel source dissolved in 12 mL of organic solvent has a molar concentration of 0.4-2.4 mmol.
5. The preparation method according to claim 1, characterized in that, The hydrothermal reaction is carried out at a temperature of 100-180 ℃ for 8-24 h.
6. The preparation method according to claim 1, characterized in that, The manganese source in the 40 mL aqueous solution containing the manganese source and regulator includes at least one of manganese nitrate, manganese chloride, and manganese acetate; And / or, the amount of manganese source added is 0.6 mmol, and the amount of regulator added is 0.9 mmol; And / or, the pH of the aqueous solution containing the manganese source and regulator is 9-12.
7. The preparation method according to claim 1, characterized in that, The liquid phase immersion treatment time is 8-24 h.
8. A nickel-manganese-based catalyst, characterized in that, The nickel-manganese-based catalyst is prepared by the preparation method according to any one of claims 1-7.
9. The use of the nickel-manganese-based catalyst of claim 8 in the electrocatalytic oxidation of 5-hydroxymethylfurfural to prepare 2,5-furandicarboxylic acid.
10. A method for preparing 2,5-furandicarboxylic acid by electrocatalytic oxidation of 5-hydroxymethylfurfural, wherein the method uses the nickel-manganese-based catalyst of claim 8 as the working electrode or a working electrode modification material.